The Model Media Audiovisual Sebagai Media Pembelajaran BIPA Untuk Mengenalkan Kosakata Bahasa Batak Pakpak Melalui Cerita Rakyat - Nissa, Khairunissa; Ginting, Pivi Turbana Br; Wibowo, Setiyo; Syahfitri, Dian (LPPM Universitas PGRI Silampari Lubuklinggau, 2025)
This research aims to develop and analyze the use of audiovisual media as a medium for learning Indonesian for Foreign Speakers (BIPA) in introducing Batak Pakpak language vocabulary through the folklore